Surface micromachining multilayer porous silicon for spectral filtering applications. (February 2022) - Afandi, Yaman; Parish, Giacinta; Keating, Adrian
Abstract: Novel micromachining processes were developed to produce optical filters operating in the long-wave infrared region (8–12 μm). The filters were composed of a multilayer porous silicon top mirror and silicon bottom mirror separated by air cavity. Release of the top mirror membranes (with sizes ranging between 300 × 300 μm 2 and 600 × 600 μm 2 ) was achieved using electropolishing. Inclusion of stress-relief notches in the top mirror (the suspended structure) improved both the flatness and the yield. Due to the high porosity of the films, a key finding was the need to reduce the plasma power during the etching process, to reduce damage to the film. The optical response of the device was evaluated by comparing the measured transmittance to the model, with favourable results confirming the future potential application of this technology for long wave infrared spectral filtering.